THE INFLUENCE OF INNOVATICS OF HIGHER EDUCATION AND SCIENCE ON THE FORMATION OF A KNOWLEDGE SOCIETY IN UKRAINE - Oleksandr Romanovskyi; Yuliia Romanovska; Oleksandra Romanovska (Baltic Journal of Economic Studies, 2024)
The subject of this research is to present and describe the impact of the mechanisms of higher education and science innovatics on the formation of the knowledge society in Ukraine. The purpose of this study is to analyse the pivotal role of higher education and science innovatics in the formation of a knowledge society in Ukraine, encompassing both the information and innovation societies. The research methodology employed in this study is based on an objective, standardised approach to the analysis of factual data on innovation activities in the field of higher education and science. This includes the development and implementation of innovation policy in higher education systems and in the world's leading universities, the latest published results of experiments, as well as materials from sources of scientific literature on innovation policy and innovation management in the field of building information and innovation societies interconnected with the knowledge society. Results. The authors formulate the necessary and sufficient conditions for rebuilding a knowledge society in Ukraine. The necessary conditions include the following: consolidation of all existing political forces in Ukraine, civil society and every individual around the idea of building a knowledge society in the country and overcoming significant corruption in all echelons of power; formation of public intolerance to manifestations of corruption and bribery by officials and all members of society. The accelerated post-war reconstruction and further development of Ukraine's industrial, production facilities, and economic infrastructure led to an expansion of the influence of the market economy on economic and social reforms. Furthermore, the advancement of science and education, along with the enhancement of the intellectual capacity of the Ukrainian population, has led to the creation and implementation of effective scientific and technical theoretical, methodological, and practical tools for the innovative development of higher education and science. Among the sufficient conditions are the following: a developed industrial and economic infrastructure, a developed intellectual civil society, a developed and flexible legal system, and a developed information and innovation base of society. The article also shows that in Ukrainian society, higher education and science are not only branches (spheres) of the national economy, but also human-oriented socio-economic processes that have social and economic components. It is therefore evident that the innovatics within higher education and science have a considerable influence on the country's socio-economic development. Conclusion. The article presents an overview of the areas in which innovative changes in higher education and science are taking place, influencing the formation of a knowledge society in Ukraine. These areas are of interest for further research and development in this sphere.